EDUCAÇÃO E SOCIALIDADE: aspectos do imaginário na Banda de Música do Bom Menino - Lima, Suely Simone Costa (2006)
This paper searches to try to investigate music as symbolical practical organizer of the sociality of the group that composes the Band of Music of the Bom Menino of the Convento das Mercês formed by children and adolescents. In a perspective of Culturanálise de Grupo deriving of from the study of the Anthropology of the Organizations and the Education, area that reveals the imaginary as a pedagogical power of the imagination and questioning the deplete of a vision of rational world. It was intended to realize a reflection about the man in a byo-psyco-socio-cultural boarding in a transdisciplinar perspective about the Sciences and the Knowledge passing for a review of paradigms to become a more complete reading of citizen. It tries to investigate through the literature and familiarity on ambient the possible elements to clear the significant social changes that can a effect children and adolescents involved in actives whith music. Privileges, too, the need to study who is outside of the traditional class without losing the questioning who the imaginary can be, too, an organized place on education and social insertion. The theoretical principles of reference were, Gilbert Durand on the imaginary, in Sociology, Michel Maffesoli, and the intricate Anthropology of Edgar Morin, beyond that contribution of some concepts of Psychoanalysis, Education and Psychology